The altruistic and redistributive effects of emigration - Žerjal, Borut (Dve domovini, 2025)
The article looks at the effects of emigration through altruistic and redistributive uses of remittances sent and earnings brought back home by emigrants. Through case studies of altruistic and redistributive mechanisms, it explores the roles of family strategies and processes of commonization through the public administration of legacies and benefices, focusing on testamentary legacies and ecclesiastical benefices created by emigrants in their places of origin in Italian Switzerland during the 18th and 19th centuries.
Keywords: charity; dobrodelnost; družina; effects of emigration; family; filantropija; migracije; migration; philanthtrophy; učinki emigracije